HORIZONTAL WELL HYDRAULICS IN LEAKY AQUIFERS - Zhan H.; Park E. (My University, 2003)
This paper presents a general study of horizontal well hydraulics for three aquifer types: a leaky confined aquifer, a leaky water table aquifer, and a leaky aquifer under a water reservoir. Semi-analytical solutions are obtained for cases that exclude and include the aquitard storage. The type curves and derivative type curves for these different conditions are provided. A graphically integrated MATLAB program named HW_LEAK is written to facilitate numerical calculations and generation of the type curves and derivative type curves. This study shows that (1) derivative type curves are more sensitive to the aquitard parameters than the type curves; and that (2) drawdown is sensitive to the aquitard/aquifer thickness ratio and the hydraulic conductivity ratio at the intermediate and later time. Both curves are less sensitive to the aquitard/aquifer specific storage ratio, while the degree of sensitivity of the drawdown to the aquitard parameters is high in a leaky confined aquifer, moderate in a water table aquifer, and low in an aquifer under a water reservoir.
Keywords: GROUNDWATER FLOW; HORIZONTAL WELL; LEAKY AQUIFER; TYPE CURVES; DERIVATIVE TYPE CURVES